Summertime diurnal variations in the isotopic composition of atmospheric nitrogen dioxide at a small midwestern United States city. (April 2018) - Walters, Wendell W.; Fang, Huan; Michalski, Greg
Abstract: The nitrogen and oxygen stable isotopes (δ 15 N & δ 18 O) of nitrogen oxides (NOx  = nitric oxide (NO) + nitrogen dioxide (NO2 )) may be a useful tool for partitioning NOx emission sources and for evaluating NOx photochemical cycling, but few measurements of in situ NOx exist. In this study, we have collected and characterized the diurnal variability in δ 15 N and δ 18 O of NO2 from ambient air at a small Midwestern city (West Lafayette, IN, USA, 40.426° N, 86.908° W) between July 7 to August 5, 2016, using an active sampling technique. Large variations were observed in both δ 15 N(NO2 ) and δ 18 O(NO2 ) that ranged from −31.4 to 0.4‰ and 41.5–112.5‰, respectively. Daytime averages were −9.2 ± 5.7‰ (x̅ ± 1σ) and 86.5 ± 14.1‰ (n = 11), while nighttime averages were −13.4 ± 7.3‰ and 56.3 ± 7.1‰ (n = 12) for δ 15 N(NO2 ) and δ 18 O(NO2 ), respectively. The large variability observed in δ 15 N(NO2 ) is predicted to be driven by changing contributions of local NOx emission sources, as calculated isotope effects predict a minor impact on δ 15 N(NO2 ) relative to δ 15 N(NOx ) that is generally less than 2.5‰ under the sample collection conditions of high ozone concentration ([O3 ]) relative to [NOx ]. A statistical δ 15 N mass-balance model suggests that traffic-derived NOx is the main contributor to the sampling site (0.52 ± 0.22) with higher relative contribution during the daytime (0.58 ± 0.19) likely due to higher traffic volume than during the nighttime (0.47 ± 0.22). The diurnal cycle observed in δ 18 O(NO2 ) is hypothesized to be a result of the photochemical cycling of NOx that elevates δ 18 O(NO2 ) during the daytime relative to the nighttime. Overall, this data suggests the potential to use δ 15 N(NO2 ) for NOx source partitioning under environmental conditions of high [O3 ] relative to [NOx ] and δ 18 O(NO2 ) for evaluating VOC-NOx -O3 chemistry. Highlights: Isotopic analysis (δ 15 N & δ 18 O) was performed on collected in situ NO2. δ 15 N(NO2 ) indicates vehicle emissions are the dominant NOx emission source. A δ 18 O(NO2 ) diurnal cycle was observed, reflecting NOx photochemistry. δ 18 O(NO2 ) maybe a useful new tool for evaluating VOC-NOx -O3 chemistry.